2021
DOI: 10.1177/1362361320984313
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing developmental–behavioral pediatric rotations by teaching residents how to evaluate autism in primary care

Abstract: Most pediatric residency programs do not provide adequate practical experiences for residents in autism-related care, with a specific dearth of training in diagnostic processes. Without this training, residents enter the primary care workforce with uncertainty surrounding implementation of standard-of-care recommendations for children with autism. Our curriculum was designed to improve upon previously passive shadowing experiences within our developmental–behavioral pediatric rotation by integrating hands-on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In the current study, about half of the pediatricians and nearly 20% of the residents knew that the onset of symptoms and findings in early childhood was a diagnostic criterion. These low rates show that a structured, hand-on "child psychiatry" training should be a must in pediatric residency training as well as the undergraduate curriculum to ensure early diagnosis and early intervention for optimal outcome (Hine et al, 2021).…”
mentioning
confidence: 99%
“…In the current study, about half of the pediatricians and nearly 20% of the residents knew that the onset of symptoms and findings in early childhood was a diagnostic criterion. These low rates show that a structured, hand-on "child psychiatry" training should be a must in pediatric residency training as well as the undergraduate curriculum to ensure early diagnosis and early intervention for optimal outcome (Hine et al, 2021).…”
mentioning
confidence: 99%
“…It is also important to note that most of the training programs, even those that occurred exclusively online, had some live interactive component. The remaining three non-ECHO training programs (1 medium-quality and 2 low-quality) employed a hybrid model consisting of both online and in-person components and were highly variable in duration, ranging from one day to a few months (Carbone et al, 2016; Havercamp et al, 2016; Hine et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Physician self-efficacy was the second outcome measure assessed in this literature review, and all of the identified studies measuring self-efficacy found significant improvements in the outcome measure following the completion of a specialized autism training program (Table 1). For example, one study found that physicians became more comfortable with identifying the symptoms of ASD, making appropriate diagnoses and referrals, and providing care to autistic children (Hine et al, 2021). Another study found that levels of self-efficacy remained increased six months following the completion of a training program (van ‘t Hof et al, 2021), suggesting that these educational programs are able to have a lasting impact on physicians’ confidence in their ability to provide care to autistic individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also recent feasibility data on incorporating ASD diagnostic assessment into pediatric residency training, which may also enhance community capacity. 30 Furthermore, eligibility for supports and services may depend on including measures (e.g., adaptive skills or other relevant functional domains) that may be less accessible to PCPs than to specialized teams. Mitigating strategies are possible.…”
Section: Discussionmentioning
confidence: 99%